ANALISIS KINERJA PEGAWAI DARI PENILAIAN BUDAYA KERJA, MOTIVASI DAN SEMANGAT KERJA (Studi Pada Dinas Peternakan dan Kesehatan Hewan Kabupaten Bireuen) - Safrizal, Safrizal; M.; Mahyu (LPPM-UNIKI, 2024)
The research aims to analyze employee performance from the aspects of work culture, motivation and work spirit. With research on employees of the Bireuen Regency Animal Husbandry and Health Service. Using a survey based on a questionnaire instrument asked to employees. The approach used is a quantitative approach, with analysis using the path association model. The research results show: 1) Employee performance is influenced both directly and indirectly by work culture by 43.6%. 2) Employee performance is positively related to employee work motivation, and the influence is significant, both directly and indirectly, at 44.2%. 3) Apart from that, the work morale factor has quite a large influence both directly and indirectly, namely 33.36%. 4) Simultaneously, work culture, motivation and work enthusiasm have a positive effect on the performance of Bireuen Regency Animal Husbandry and Health Service employees, namely 65%.